Adherence and perceptions regarding simulation training in undergraduate health Sciences - Elias,Fernando Perpétuo (2010)
BACKGROUND: Simulation techniques are spreading rapidly in medicine. Suc h resources are increasingly concentrated in Simulation Laboratories. The MSRP-USP is structuring such a laboratory and is interested in the prevalence of individual initiatives that could be centralized there. The MSRP-USP currently has five full-curriculum courses in the health sciences: Medicine, Speech Therapy, Physical Therapy, Nutrition, and Occupational Therapy, all consisting of core disciplines. GOAL: To determine the prevalence of simulation techniques in the regular courses at MSRP-USP. METHODS: Coordinators of disciplines in the various courses were interviewed using a specifically designed semi-structured questionnaire, and all the collected data were stored in a dedicated database. The disciplines were grouped according to whether they used (GI) or did not use (GII) simulation resources. RESULTS AND DISCUSSION: 256 disciplines were analyzed, of which only 18.3% used simulation techniques, varying according to course: Medicine (24.7.3%), Occupational Therapy (23.0%), Nutrition (15.9%), Physical Therapy (9.8%), and Speech Therapy (9.1%). Computer simulation programs predominated (42.5%) in all five courses. The resources were provided mainly by MSRP-USP (56.3%), with additional funding coming from other sources based on individual initiatives. The same pattern was observed for maintenance. There was great interest in centralizing the resources in the new Simulation Laboratory in order to facilitate maintenance, but there was concern about training and access to the material. CONCLUSIONS: 1) The MSRP-USP simulation resources show low complexity and are mainly limited to computer programs; 2) Use of simulation varies according to course, and is most prevalent in Medicine; 3) Resources are scattered across several locations, and their acquisition and maintenance depend on individual initiatives rather than central coordination or curricular guidelines